2019
DOI: 10.2337/dc19-0078
|View full text |Cite
|
Sign up to set email alerts
|

A Lack of Decline in Major Nontraumatic Amputations in Texas: Contemporary Trends, Risk Factor Associations, and Impact of Revascularization

Abstract: Nontraumatic major lower extremity amputations (LEAs) have been reported to be declining nationally; however, trends in Texas have been less well described. We evaluated demographic and clinical risk factors and revascularization associations for LEAs by using inpatient hospital discharge data in Texas from 2005 to 2014. RESEARCH DESIGN AND METHODS Inpatient hospital discharge data were obtained from the Texas Center for Health Statistics. Multivariate logistic regression analyses were performed to evaluate cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…Clinical profiles might be different between the two revascularization procedures, although recent clinical studies have shown that major patient backgrounds are not so largely different between them in clinical practice [39, 40]. On the other hand, previous studies suggested that patient attributes would be different between LE-PAD patients undergoing revascularization and those undergoing primary amputation [41]. Future studies in other countries will be needed to validate the current findings.…”
Section: Discussionmentioning
confidence: 80%
“…Clinical profiles might be different between the two revascularization procedures, although recent clinical studies have shown that major patient backgrounds are not so largely different between them in clinical practice [39, 40]. On the other hand, previous studies suggested that patient attributes would be different between LE-PAD patients undergoing revascularization and those undergoing primary amputation [41]. Future studies in other countries will be needed to validate the current findings.…”
Section: Discussionmentioning
confidence: 80%
“…The clinical factors associated with LEA were selected based on previous studies. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 Stages of CKD were determined using the mean level of outpatient estimated glomerular filtration rate (eGFR) in that year 40 : eGFR greater than or equal to 60 mL/min/1.73 m 2 was defined as no CKD, eGFR between 45 and 59 mL/min/1.73 m 2 was defined as CKD 3A, eGFR between 30 and 44 mL/min/1.73 m 2 was defined as CKD 3B, and eGFR between 15 and 29 mL/min/1.73 m 2 was defined as CKD 4. CKD 5 was defined as eGFR less than 15 mL/min/1.73 m 2 with no history of kidney transplantation or dialysis.…”
Section: Methodsmentioning
confidence: 99%
“…1 In many regions, persons with lower socioeconomic status have a higher prevalence of CKD, limited access to treatment, and poorer outcomes. [2][3][4][5] Early identification of CKD by screening for kidney disease, followed by risk stratification and treatment, offers the potential to substantially reduce the morbidity and mortality from CKD and its related complications, such as cardiovascular disease. 6,7 However, at present, there is no accepted systematic strategy for CKD screening and treatment.…”
Section: Introductionmentioning
confidence: 99%